مخرجات برنامج تدريبي مقترح لتطوير صفة القوة الانفجارية لدى سباحي الفئة العمرية 12 - 13 سنة في تقنية الدوران - طلبي شكري (My University, 2025)
ملخص الدراسة: هدفت هذه الدراسة إلى استكشاف كيف يمكن لبرنامج تدريبي مصمم خصيصاً لتحسين القوة الانفجارية لدى السباحين الصغار الذين تتراوح أعمارهم بين 12 و13 عاماً، مع التركيز بشكل خاص على تحسين تقنية الدوران لديهم - وهي مهارة حاسمة غالباً ما تحدث فرقاً في سباقات السباحة التنافسية. وقد جمع البرنامج بين التمارين البليومترية جيدة التنظيم والتمارين القائمة على القوة التي تم تصميمها لتناسب الاحتياجات البدنية والنمائية لهذه الفئة العمرية. وقد تم تطبيقه على مجموعة من عشرة سباحين من نادي AJM، وجميعهم يشتركون في خصائص متشابهة من حيث العمر والوزن والخبرة ومستوى الأداء. لتقييم فاعلية البرنامج، اتبعت الدراسة تصميمًا تجريبيًا قبل وبعد الاختبار باستخدام اختبار القفز المضاد للحركة (CMJ)، والذي يقيس القوة الانفجارية النسبية للسباحين بالواط لكل كيلوغرام (W/Kg). تم استخدام العديد من الأدوات الإحصائية، بما في ذلك اختبار شابيرو-ويلك لقياس الحالة الطبيعية والإحصاءات الوصفية الأساسية ومعيار كوهين د لحساب حجم التأثير. أظهرت النتائج تحسنًا واضحًا وهادفًا. زاد متوسط القوة الانفجارية للمجموعة من 13.69 واط/كجم قبل البرنامج إلى 14.61 واط/كجم بعده. كان حجم التأثير معتدلًا (د = 0.66)، مما يشير إلى أن التغييرات لم تكن مجرد صدفة - بل كانت نتيجة التدريب نفسه. تدعم هذه النتائج الفرضيات الأولية وتؤكد على قيمة برامج التدريب المنظمة التي تركز على القوة التفجيرية. بالنسبة للرياضيين الشباب، وخاصة السباحين، فإن مثل هذه التمارين المستهدفة Study Summary: This study set out to explore how a specifically designed training program could improve explosive strength in young swimmers aged 12 to 13 years, particularly focusing on enhancing their turning technique—a critical skill that often makes the difference in competitive swimming races. The program combined well-structured plyometric and power-based exercises that were tailored to fit the physical and developmental needs of this age group. It was applied to a group of ten swimmers from the AJM club, all of whom shared similar characteristics in terms of age, weight, experience, and performance level. To evaluate the effectiveness of the program, the study followed a pre-post experimental design using the Countermovement Jump (CMJ) test, which measured the swimmers’ relative explosive power in watts per kilogram (W/Kg). Several statistical tools were used, including the Shapiro-Wilk test for normality, basic descriptive statistics, and Cohen’s d for calculating effect size. The results showed a clear and meaningful improvement. The group’s average explosive power increased from 13.69 W/Kg before the program to 14.61 W/Kg afterward. The effect size was moderate (d = 0.66), indicating that the changes weren’t just by chance—they were the result of the training itself. These findings support the initial hypotheses and emphasize the value of structured training programs that focus on explosive strength. For young athletes, especially swimmers, such targeted exercises can build the foundation for better technique, more efficiency in the water, and ultimately, improved competitive results. In short, this study highlights how scientific training can be both effective and age-appropriate, and it encourages coaches and researchers alike to continue exploring smart ways to support youth athletic development. Résumé de l'étude : Cette étude visait à explorer comment un programme d'entraînement spécifiquement conçu pouvait améliorer la force explosive chez les jeunes nageurs âgés de 12 à 13 ans, en se concentrant particulièrement sur l'amélioration de leur technique de virage - une compétence critique qui fait souvent la différence dans les courses de natation de compétition. Le programme combinait des exercices plyométriques et de puissance bien structurés, adaptés aux besoins physiques et au développement de ce groupe d'âge. Il a été appliqué à un groupe de dix nageurs du club AJM, qui présentaient tous des caractéristiques similaires en termes d'âge, de poids, d'expérience et de niveau de performance. Pour évaluer l'efficacité du programme, l'étude a suivi un plan expérimental pré-post en utilisant le test CMJ (Countermovement Jump), qui mesure la puissance explosive relative des nageurs en watts par kilogramme (W/Kg). Plusieurs outils statistiques ont été utilisés, notamment le test de normalité de Shapiro-Wilk, des statistiques descriptives de base et le d de Cohen pour calculer la taille de l'effet. Les résultats ont montré une amélioration claire et significative. La puissance explosive moyenne du groupe est passée de 13,69 W/Kg avant le programme à 14,61 W/Kg après. L'ampleur de l'effet était modérée (d = 0,66), ce qui indique que les changements n'étaient pas le fruit du hasard, mais bien le résultat de l'entraînement lui-même. Ces résultats confirment les hypothèses initiales et soulignent la valeur des programmes d'entraînement structurés axés sur la force explosive. Pour les jeunes athlètes, en particulier les nageurs, de tels exercices ciblés.
Keywords: البرنامج التدريبي; القوة الإنفجارية; سباحي الفئة العمرية 12 – 13 سنة; تقنية الدوران.; Training program; explosive power; 12-13 year old swimmers; rotational technique; Programme d'entraînement; Force explosive; Nageurs de 12-13 ans; Technique de rotation